2021
DOI: 10.1107/s2059798321009542
|View full text |Cite
|
Sign up to set email alerts
|

Ambiguities in and completeness of SAS data analysis of membrane proteins: the case of the sensory rhodopsin II–transducer complex

Abstract: Membrane proteins (MPs) play vital roles in the function of cells and are also major drug targets. Structural information on proteins is vital for understanding their mechanism of function and is critical for the development of drugs. However, obtaining high-resolution structures of membrane proteins, in particular, under native conditions is still a great challenge. In such cases, the low-resolution methods small-angle X-ray and neutron scattering (SAXS and SANS) might provide valuable structural information.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 92 publications
0
8
2
Order By: Relevance
“…The plot has a maximum value of 1.120 at qR g = 1.786, which is very close to the properties of the peak in the case of ideally globular particles (1.104 at qR g = 3) 70 . A peak shift towards higher qR g values could indicate partial disorder or an elongated protein shape 71,72 , but this was not observed in our data.…”
Section: Methodscontrasting
confidence: 88%
“…The plot has a maximum value of 1.120 at qR g = 1.786, which is very close to the properties of the peak in the case of ideally globular particles (1.104 at qR g = 3) 70 . A peak shift towards higher qR g values could indicate partial disorder or an elongated protein shape 71,72 , but this was not observed in our data.…”
Section: Methodscontrasting
confidence: 88%
“…The plot has a maximum value of 1.120 at qR g = 1.786, which is very close to the properties of the peak in the case of ideally globular particles (1.104 at qR g = √3) ( Burger et al, 2016 ). A peak shift toward higher qR g values could indicate partial disorder or an elongated protein shape ( Ryzhykau et al, 2021a ; Ryzhykau et al, 2021b ), but this was not observed in our data.…”
Section: Methodscontrasting
confidence: 81%
“…Therefore, the direct application of these classical ab initio approaches to the SAXS data obtained for MPs may provide misleading results. For example, the presence of detergents or lipids bound to MPs results in the appearance of scattering intensity maxima at q ≈ 0.1–0.2 Å −1 (demonstrated for the sensory rhodopsin II/transducer complex from Natronomonas pharaonis [ 158 , 159 ]). In SMA-solubilized lipodiscs, the polymer may be located not only at the rim of the lipodisc, but also on its surface, affecting the scattering intensity [ 65 ].…”
Section: Applications Of Lipodiscs In Structural Biologymentioning
confidence: 99%